PENEGAKAN HUKUM DALAM TINDAK PIDANA SIBER PENCEMARAN NAMA BAIK MELALUI PENDEKATAN HUKUM PROGRESIF - Aldie Rangga Diputra; Imas Rosidawati Wiradirja; Deny Haspada (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2022)
ABSTRACT Cybercrime law enforcement often creates controversy among the public, this is because on the one hand conveying something, whether criticizing or arguing against something, is still vulnerable to someone being punished even though someone issues an opinion or assessment that aims to build and does not intend to defame dignity. or degrade the dignity of the criticized, on the other hand this is protected and passed by law. Based on this phenomenon, this study will examine the enforcement and application of law in cybercrimes through a progressive legal approach. The research method used is a combination of a normative approach and an empirical method. By combining these two methods, namely seeing the reality on the ground by explaining the provisions in the applicable laws and regulations. The results of this study indicate that the enforcement of cybercrime, especially defamation, and the implementation of several articles on cybercrime have been agreed to serve as implematic guidelines for law enforcers. Cybercrime of defamation in Indonesia mainly must be underlined and remembered that the law is for humans, not humans for the law, from this explanation it can be concluded that law can create an atmosphere of happiness, prosperity and provide a sense of security for every human being who is facing it. Keywords: Progressive Law, Enforcement, Cybercrime